Effect of rotating arc process on molten pool control in horizontal welding. (July 2014) - Guo, N.; Wang, M. R.; Guo, W.; Yu, J. B.; Feng, J. C.
<x content-type="archive" xml:space="preserve">Abstract</x> This paper describes the effect of rotating arc process on molten pool control in narrow gap horizontal welding. From energy strategy and force strategy, technical advantages of rotating arc process in molten pool control are explored. On the one hand, because of the decrease of temperature and holding time in weld centre, rotating arc process limits the tendency of molten pool sagging with the arc rotating frequency no more than 10 Hz, which is indicated from the simulation results of heat distribution characteristics. On the other hand, rotating arc process induces the flow of molten metal in the weld width direction by the periodical effect of arc force and droplets impingement, which is observed by the high speed photography system. This oscillation propels the molten metal at lower side against the effect of gravity to flow to the upper side, which is beneficial for the molten pool formation of horizontal welding.